Depilado enzimático conservador del pelo: injuria química y mecánica de la epidermis para incrementar los procesos difusivos - Garro, María Laura (2012)
In bovine skin the main barrier for substances is located in the upper layer, stratum corneum, where intercellular lipids play a crucial role as hydrophobic barrier. This barrier must be transformed to allow enzymes reach the pilosebaceous unit and basal lamina without collagen damage. In the present study in bovine epidermis, surfactants and sodium sulphite where employed as pretreatment before trypsin. Bicarbonate buffer was used as control. Samples where analyzed with histological techniques, transmission electron microscopy, stain diffusion and spectroscopy. Skin morphology and stain permeability changed after the treatments. Loss of desmosomes observed with TEM could be consequence of trypsin. Persistence of the basal lamina after trypsin could be associated with the period of time used to study enzyme activity. Sulphite pretreatment caused disorganization of collagen fibrils, dermis -epidermis separation and increased stain diffusion. Also when sulphite was combined with reagents its effect decreased. Statistical studies applied in vibrational spectra of stratum corneum lipids demonstrate no alteration by terpenes.